The Peruvian romantics and the conflict with Spain (1864-1866) - Holguín Callo, Oswaldo (2023)
Peruvian romantics participated outstandingly in the literary production of the years 1840 to 1880. Despite having been formed in an anti-Spanish political environment, inherited from previous generations and the War of Independence, the talent of the Hispanic romantics attracted them and turned them into their admirers and followers. During the War with Spain (1864-1866), the Peruvian romantics played a very important role thanks to their rich patriotic and nationalist poetry, read and recited on many occasions, and disseminated by diverse means. Their works recreated some pages of the History of Peru as well as censures to the Spaniards of the Conquest and the Viceroyalty. Keywords: Peruvian romantics, Spanish writers, War with Spain (1864-1866), patriotic poetry, History of Peru.